Analisis Hubungan Keaktifan Berorganisasi Terhadap Hasil Prestasi Akademik Mahasiswa Fakultas Ekonomi Universitas Negeri Surabaya - Ahmad Ali Fauzi; Triesninda Pahlevi (Universitas Negeri Surabaya, 2020)
Organization is something container for actualize self and reach aims together as students. While that college student have task main that is learn. There college student Major Faculty Economics of State University Surabaya in organization have achievement higher learning this interesting for reviewed. The aim of this research is to describe about students who active organization in Faculty Economics of State University Surabaya concerned with their role and status as student and member of its organization. This research uses a case study qualitative research method and using descriptive data analyzing technique. The research data was taken from primary data through interviews and secondary data from books, literature, articles, internet, and journals related to this study. The results showed that students became more confident, so as to improve learning achievement. This is shown by the results of the cumulative grade point average (GPA) which is very satisfying. In addition, by participating in student organization activities, students can improve soft skills in terms of engaging with other parties and can create a spirit of leadership.